Temporal pattern of de novo lipogenesis in the postprandial state in healthy men - TIMLIN, Maureen T; PARKS, Elizabeth J (The American journal of clinical nutrition, 2005)
Recent data suggest that hepatic de novo lipogenesis (DNL) is elevated in the fed state compared with the fasting state, but the rate at which lipogenesis can increase with meal consumption is currently unknown. The objective was to quantify the diurnal pattern of lipogenesis after 2 consecutive mixed meals were fed to healthy men (n = 8). A liquid diet was administered after a 12-h fast. During the fasting and postprandial periods, serum insulin, glucose, triacylglycerol, and nonesterified fatty acid concentrations were measured, and rates of DNL were quantified via intravenous infusion of [1-(13)C] sodium acetate and mass isotopomer distribution analysis. The temporal pattern of postprandial lipogenesis was similar in all subjects. Lipogenesis rose significantly from 4.7 +/- 3.3% at fasting, peaked at 18.2 +/- 7.1% after meal 1 (P = 0.003 compared with fasting), rose further to 23.1 +/- 8.9% after meal 2 (P = 0.01 for difference between meals), and then decreased toward baseline (P < 0.001). Lipogenesis peaked 4.2 h after the meals; lipoprotein-triacylglycerol concentrations peaked sooner, 2.0 h after the meals (P < 0.02). Maximum postprandial DNL ranged from 10.3% to 37.5%. Peak insulin concentrations after meal 1 correlated with peak DNL (R = 0.838, P = 0.037), although the leanest subjects had some of the highest rates of postprandial DNL. These data confirm the acute stimulation of DNL after meals in healthy subjects and validate the contribution of this pathway to elevations in triacylglycerol concentration.